응급실 간호사의 안전간호활동 영향요인 - 배효선; 서은지; Pae, Hyo Seon; Seo, Eun Ji (Chunghwanja Kanho Hakhoe chi, 2025)
Purpose : The purpose of this study was to investigate the level of communication ability, team psychological safety, patient safety competency, and safety nursing activities of emergency room nurses and to identify factors that affect safety nursing activities. Methods : Data were collected from 117 nurses working in emergency departments in Gyeonggi-do from May 2024 to August 2024. Results : The mean age of the study participants was 29.64±4.56 years, and 77.8% were female. The mean scores of communication ability, team psychological safety, patient safety competency, and safety nursing activities were 3.81±0.45 (of 5), 30.88±5.90 (of 49), 3.99±0.38 (of 5), and 4.23±0.42 (of 5) points, respectively. Skill in patient safety competency ( =.38, p<.001), knowledge in patient safety competency ( =.32, p<.001), and training on patient safety ( =.20, p =.003) were significantly associated with safety nursing activities. Conclusion : Skill and knowledge in patient safety competency were found to have a significant impact on the safe nursing activities of emergency department nurses. Therefore, systemic and active education is needed to increase nurses' patient safety capabilities.